Quantitative microbial faecal source tracking with sampling guided by hydrological catchment dynamics - G. H. Reischer; J. M. Haider; R. Sommer; H. Stadler; K. M. Keiblinger; R. Hornek; W. Zerobin; R. L. Mach; A. H. Farnleitner (Environmental Microbiology, 2008)
Summary The impairment of water quality by faecal pollution is a global public health concern. Microbial source tracking methods help to identify faecal sources but the few recent quantitative microbial source tracking applications disregarded catchment hydrology and pollution dynamics. This quantitative microbial source tracking study, conducted in a large karstic spring catchment potentially influenced by humans and ruminant animals, was based on a tiered sampling approach: a 31‐month water quality monitoring (Monitoring) covering seasonal hydrological dynamics and an investigation of flood events (Events) as periods of the strongest pollution. The detection of a ruminant‐specific and a human‐specific faecal Bacteroidetes marker by quantitative real‐time PCR was complemented by standard microbiological and on‐line hydrological parameters. Both quantitative microbial source tracking markers were detected in spring water during Monitoring and Events, with preponderance of the ruminant‐specific marker. Applying multiparametric analysis of all data allowed linking the ruminant‐specific marker to general faecal pollution indicators, especially during Events. Up to 80% of the variation of faecal indicator levels during Events could be explained by ruminant‐specific marker levels proving the dominance of ruminant faecal sources in the catchment. Furthermore, soil was ruled out as a source of quantitative microbial source tracking markers. This study demonstrates the applicability of quantitative microbial source tracking methods and highlights the prerequisite of considering hydrological catchment dynamics in source tracking study design.